Identifying research priorities for digital technology in mental healthcare: results of the James Lind Alliance Priority Setting Partnership - Hollis, Chris; Sampson, Stephanie; Simons, Lucy; Davies, E. Bethan; Churchill, Rachel; Betton, Victoria; Butler, Debbie; Chapman, Kathy; Easton, Katherine; Gronlund, Toto Anne; Kabir, Thomas; Rawsthorne, Mat; et al. (Lancet, 2018)
Digital technology, including the use of internet, smartphones and wearables, holds the promise to bridge the mental health treatment gap by offering a more accessible, potentially less stigmatising, flexible and tailored approach to mental healthcare. However, the evidence-base for digital mental health interventions and demonstration of clinical- and cost-effectiveness in real-world settings remains inadequate. The James Lind Alliance (JLA) Priority Setting Partnership (PSP) for digital technology in mental healthcare was established to identify research priorities that reflected the perspectives and unmet needs of people with lived experience of mental health problems, mental health service users, their carers, and healthcare practitioners. 644 participants contributed over 1350 separate questions, which were reduced by qualitative thematic analysis into six overarching themes. Following removal of out of scope questions and a comprehensive search of existing evidence, 134 questions were verified as uncertainties suitable for research. These questions were then ranked online and in workshops by 628 participants to produce a shortlist of 26. The top ten research priorities were identified by consensus at a stakeholder workshop. The top ten priorities should inform research policy and funding in this field. Identified priorities primarily relate to the safety and efficacy of digital technology interventions in comparison with face to face interventions, evidence of population reach, mechanisms of therapeutic change, and how best to optimize the effectiveness of digital interventions in combination with human support.